DIY music and the politics of social media - Jones, Ellis (Bloomsbury Academic, 2021)
"An investigation into the contemporary practices of DIY musicians on social media and DIY's status as "cultural resistance.""--
Keywords: Geschichte; Social Media; Marketing; Musiker; Popular music / Social aspects; Music trade / Social aspects; Social media